2018
DOI: 10.1016/j.neuroimage.2017.10.019
|View full text |Cite
|
Sign up to set email alerts
|

A functional connectivity-based neuromarker of sustained attention generalizes to predict recall in a reading task

Abstract: Sustaining attention to the task at hand is a crucial part of everyday life, from following a lecture at school to maintaining focus while driving. Lapses in sustained attention are frequent and often problematic, with conditions such as attention deficit hyperactivity disorder affecting millions of people worldwide. Recent work has had some success in finding signatures of sustained attention in whole-brain functional connectivity (FC) measures during basic tasks, but since FC can be dynamic and task-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 52 publications
(79 reference statements)
5
39
0
Order By: Relevance
“…MTG responds more strongly to memory-based and meaning-based decisions, consistent with the location of this cluster at the anterior end of the ventral visual stream and yet also within the DMN (Murphy et al, 2018). In line with these studies, the anterior and middle temporal lobe have been identified as important for text comprehension (Ferstl, Neumann, Bogler, & Von Cramon, 2008;Jangraw et al, 2018;Kuperberg, Lakshmanan, Caplan, & Holcomb, 2006). Nevertheless, activation within MTG is insufficient for comprehensionour results suggest this region also needs to be strongly activated by visual inputs and to interact with other regions of DMN implicated in comprehension.…”
Section: Discussionsupporting
confidence: 71%
“…MTG responds more strongly to memory-based and meaning-based decisions, consistent with the location of this cluster at the anterior end of the ventral visual stream and yet also within the DMN (Murphy et al, 2018). In line with these studies, the anterior and middle temporal lobe have been identified as important for text comprehension (Ferstl, Neumann, Bogler, & Von Cramon, 2008;Jangraw et al, 2018;Kuperberg, Lakshmanan, Caplan, & Holcomb, 2006). Nevertheless, activation within MTG is insufficient for comprehensionour results suggest this region also needs to be strongly activated by visual inputs and to interact with other regions of DMN implicated in comprehension.…”
Section: Discussionsupporting
confidence: 71%
“…Multiple algorithms have been developed and used to estimate TE for continuous data. Here, we use the Kraskov, Stogbauer, and Grassberger (KSG) () technique which estimates a probability density function for a time series using Kernel estimation and alters the kernel width to adjust to the data using a nearest neighbor calculation (Lizier, ). The KSG approach is often used as the “best of breed solution” for TE estimation (Lizier, ).…”
Section: Methodsmentioning
confidence: 99%
“…One of the key goals of precision neuroscience is relating individual differences in brain data to differences in phenotypic/clinical data. Indeed, this was an important component of the original identification study (Finn et al, 2015) and much exciting work has since been conducted in this area using a variety of methods (Beaty et al, 2018;Drysdale et al, 2017;Greene et al, 2018;Hearne et al, 2016;Hsu et al, 2018;Jangraw et al, 2018;Kaufmann et al, 2017;Kong et al, 2018;Rosenberg et al, 2016;Shen et al, 2017). We were unable to add to this growing literature, because only the SLIM dataset included behavioral measures, but future work could determine if the stability of single-subject fMRI data allows predictions to be made regarding behavior at longer time frames, similar to how previous investigators have used functional connectivity measures to predict a behavioral or psychiatric score in cross-sectional studies.…”
Section: Relevance To Phenotypic Measuresmentioning
confidence: 99%